2017
DOI: 10.1021/jacs.7b08840
|View full text |Cite
|
Sign up to set email alerts
|

Self-Organized Frameworks on Textiles (SOFT): Conductive Fabrics for Simultaneous Sensing, Capture, and Filtration of Gases

Abstract: Wearable electronics have the potential to advance personalized health care, alleviate disability, enhance communication, and improve homeland security. Development of multifunctional electronic textiles (e-textiles) with the capacity to interact with the local environment is a promising strategy for achieving electronic transduction of physical and chemical information. This paper describes a simple and rapid approach for fabricating multifunctional e-textiles by integrating conductive two-dimensional (2D) me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
240
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(251 citation statements)
references
References 84 publications
11
240
0
Order By: Relevance
“…The porous structures of conductive MOFs also provide efficient conditions for the access to active sites in the materials, which can be ideal for adatom adsorptions and diffusion in energy storage systems. Previous experimental studies have confirmed that conductive MOFs can serve as promising candidates in many applications, including electrocatalysis [31,32], energy storage systems [33,34], sensors [35,36] and electronic devices [37,38]. Nevertheless, synthesize of high quality and large-area 2D MOFs are yet among the most critical challenges toward their practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…The porous structures of conductive MOFs also provide efficient conditions for the access to active sites in the materials, which can be ideal for adatom adsorptions and diffusion in energy storage systems. Previous experimental studies have confirmed that conductive MOFs can serve as promising candidates in many applications, including electrocatalysis [31,32], energy storage systems [33,34], sensors [35,36] and electronic devices [37,38]. Nevertheless, synthesize of high quality and large-area 2D MOFs are yet among the most critical challenges toward their practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Instead of using functional MOFs as filter film coating on sensing materials to provide additional selectivity and/or sensitization, EC-MOFs are novel emerging materials with regular porosity and conductivity, which are promising for chemi-resistors with high sensitivity and selectivity [76,. Unlike MOX and MOX-MOFs, which still need additional thermal or photonic energy as the trigger source to activate the sensing reaction, EC-MOFs can be directly used as sensitive materials based on their regular micro-porosity, selective frameworks, high electronic conductivity, and RT activity [139,[144][145][146][159][160][161][162][163][164][165][166]. Therefore, EC-MOFs are promising components for hybrid gas sensors and will be powerful competitors for the new generation of gas sensors.…”
mentioning
confidence: 99%
“…Moreover,t he porosity of the prepared crystalline hybrids was maintained providing ap athway to re-enforce semiconducting behavior in typically insulating porous materials (for example,covalent organic or metal-organic frameworks (COFs/MOFs)). [11][12][13][14][15][16][17][18][19][20][21] In addition to the first report of azidealkyne 1,3-cycloaddition utilized for corannulene integration in the solid state,t he described corannulene material is the first member in the family of crystalline (purely organic) donor-acceptor (D-A) corannulene-COFs with the highest surface area among corannulene-based extended structures reported to date (Scheme 1). In combination with spectroscopic and structural analysis,w ee mployed theoretical calculations,w hich allowed us to probe charge transfer rates within the Marcus theory as af unction of pBm utual orientation for the first time,a sw ell as to shed light on the density of state distribution near the Fermi edge.…”
mentioning
confidence: 99%